Application for grant to the National Science Foundation, Washington [for] an investigation into the methodology of evaluation techniques based on a test of the MEDLARS system of the National Library of Medicine - Cleverdon, Cyril W. (Cranfield University, 1965)
A grant of $55,832 is requested by Aslib from the National Science Foundation over a period of two and a half years, for the purpose of the design and direction of an investigation into the methodology of evaluation of information retrieval systems, based on an evaluation test of the MEDLARS system of the National Library of Medicine. The work involved in carrying out the test will be the financial responsibility of the Library, and this application for grant is therefore limited to those activities which will be done in England. Some general problems of evaluation methodology are considered in the paper.
Submitted by Association for Special Libraries and Information Bureaux (Aslib), London, England